Efficiently computing RKN for keyword queries on XML data - HENZi-yang C; ANGXuan W; ANGXian T (Tongxin xuebao)
Subtree results construction is a core problem in keyword query processing over XML data,for which com-puting the set of relevant keyword nodes (RKN) for each subtree's root node will greatly affect the overall system per-formance. Considering that existing methods cannot correctly identify RKN for ELCA semantics,the definitions of RKN and the RKN-Base algorithm were proposed,which can correctly judge whether a given node is an RKN of some ELCA node by sequentially scanning the set of inverted lists once. As RKN-Base cannot avoid processing all useless nodes,an optimized algorithm,namely RKN-Optimized,was then proposed,which computes RKN sets based on the set of ELCA nodes, rather than the set of inverted lists as RKN-Base does. As a result,RKN-Optimized avoids processing useless nodes, and reduces the time complexity. The experimental results verified the efficiency of the proposed algorithms.